Artificial intelligence in real time control 1994 (AIRTC'94) : a postprint volume from the IFAC symposium, Valencia, Spain, 3-5 October 1994 - Crespo, A. (Alfons) (IFAC Postprint Volume., 1995)
Artificial Intelligence is one of the new technologies that has contributed to the successful development and implementation of powerful and friendly control systems. These systems are more attractive to end-users shortening the gap between control theory applications. The IFAC Symposia on Artificial Intelligence in Real Time Control provides the forum to exchange ideas and results among the leading researchers and practitioners in the field. This publication brings together the papers presented at the latest in the series and provides a key evaluation of present and future developments of Artificial Intelligence in Real Time Control system technologies.